Developing Narrative Creavity In Class 8 At UPTD SMP Negeri 12 Pematang Siantar - Siregar, Calvyn; Selviana Napitupulu (Jurnal Ilmu Sosial dan Humaniora, 2026)
Narrative writing is an essential skill in junior high school English learning because it helps students develop creativity, language structure, and logical thinking. However, many students still face difficulties in generating ideas, organizing story structure, and using correct grammar when writing narrative texts. This study aimed to improve the narrative writing skills of Grade 8 students at UPTD SMP Negeri 12 Pematangsiantar through guided learning strategies. This research employed a descriptive qualitative method and was conducted in a real classroom setting. The participants were approximately 25–30 students from one Grade 8 class. Data were collected through narrative writing tasks, classroom observations, students’ worksheets, and field notes. The analysis focused on describing changes in students’ writing in terms of content, narrative structure, past tense usage, vocabulary, and clarity of ideas. The findings revealed that students’ narrative writing improved after receiving step-by-step guidance, including brainstorming, story planning, drafting, and teacher feedback. Students became more confident, active, and able to produce stories with clearer orientation, complication, and resolution. The classroom atmosphere also became more interactive and supportive. In conclusion, guided narrative teaching effectively enhanced students’ writing performance and engagement in learning. This study suggests that teachers should apply structured narrative instruction to help students write more creatively and accurately